Identification of a novel mutation in the CLCN7 gene in pediatric osteopetrosis: case report - Jiang, Aoshuang; Chen, Tianping; Wei, Nan; Zhu, Chenglin; Wang, Jie; Liu, Hongjun; Wang, Min (Frontiers in Pediatrics, 2025)
Osteopetrosis, also known as osteosclerosis and marble-bone disease, is a rare genetic metabolic bone disorder caused by the dysplasia or dysfunction of osteoclasts, usually caused by variants of chloride voltage-gated channel 7 (CLCN7) gene. We retrospectively analyzed the clinical data of two children with osteopetrosis and their families. Whole-exome sequencing (WES) was used for genetic analysis, and Sanger sequencing confirmed possible pathogenic variants. In family 1, the proband harbored a novel mutation c.2351G>C (p.R784T) in CLCN7 gene. The initial symptom of proband 1 was a post-traumatic fracture, and imaging features was “sandwich cake” -like changes. In family 2, the proband harbored previously reported compound heterozygous variants in CLCN7 gene: c.899C>T (p.A300V) and c.1534G>A (p.G512R). Among them, c.1534G>A (p.G512R) was only recorded in clinvar and no reports of protein function prediction. The initial symptom of proband 2 was cough, and imaging features was “sandwich vertebrae”. Our study expands the mutation spectrum of the CLCN7 gene and provides new insights into the pathogenesis of osteopetrosis.